Stress intensity factor estimation of cracks originating from square, circular or elliptical hole in a plate subjected to tension. (2022) - Vasamsetty, Ritiesh; Arunkumar, S.
Abstract: The use of Linear Elastic Fracture Mechanics (LEFM) in the assessment of reliability and performance, with the help of the concepts from Finite Elements Method, provides practical and convenient ways to study the growth of crack and fracture in the materials. While the Boundary Element Method is another tool usually used to deal with elastic fracture problems, the Finite Element Method has many powerful means to simulate and conduct experiments virtually. In this work, the influence of cracks originating from different hole shapes on the mode I Stress Intensity Factor (SIF) is analysed in Abaqus simulation package. To accomplish this, a two-dimensional finite element model of a plate containing cracks originating from square, circular or elliptical hole is created and then subjected to tension. The objective is to investigate the effect of crack length on the mode I SIF for the different shapes of holes. As the crack length is increased by 367% in all the three cases of square, circular and elliptical holes, the SIF increased respectively by 170.7%, 170.6% and 167.3%. These outcomes indicate that the magnitude of SIF increases by increasing the crack length and vice-versa. However, in the case of elliptical hole, the percent increase in SIF, is slightly less than the other two hole shapes.